1996
DOI: 10.1108/02652329610113144
|View full text |Cite
|
Sign up to set email alerts
|

Customer defection: a study of the student market in Ireland

Abstract: Relationship marketing stresses that relationships, and not just transactions, should be the focus of marketing strategy. Part of the rationale for this lies in retention economics which are thought to be particularly powerful. Recent literature suggests that reduction of the defection rate can increase profits far more than growth in market share, better margins and other factors usually associated with competitive advantage. This paper reports the findings of a detailed analysis into the defection rate of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 12 publications
1
76
0
4
Order By: Relevance
“…are wasted and further costs are required to obtain a new customer (Colgate, Steward & Kinsella, 1996;Reichheld & Sasser, 1990;Fornell & Wernerfelt, 1987). In Reichheld & Sasser's (1990) study, customer defection is seen as having a stronger ability to impact on revenue than on scale, market share, unit costs, and other factors that are usually associated with competitive advantage.…”
Section: The Effect Of Switching Behaviourmentioning
confidence: 99%
“…are wasted and further costs are required to obtain a new customer (Colgate, Steward & Kinsella, 1996;Reichheld & Sasser, 1990;Fornell & Wernerfelt, 1987). In Reichheld & Sasser's (1990) study, customer defection is seen as having a stronger ability to impact on revenue than on scale, market share, unit costs, and other factors that are usually associated with competitive advantage.…”
Section: The Effect Of Switching Behaviourmentioning
confidence: 99%
“…Reichheld (1996), reporting on the effect of defections stresses that an increase in the defection rate can lead to decrease in cash inflow to an affected organisation. It is suggested that reduction in customer defection rate is likely to lead to increase in profits substantially more than growth in market share, improved profit margins, or factors associated with competitive advantage (Colgate et al, 1996). A lot of service organisations sometimes fail to pay particular attention to customer defections, that is, customers who change service providers for competing ones.…”
Section: Customer Defection Groups Reasons For Their Defections Andmentioning
confidence: 99%
“…• Colgate et al (1996), proposed a four-step process that businesses must follow in order to reduce defection rates and capture quality and more profitable defectors: • Managers must ascertain what constitute defection rate.…”
Section: Models That Can Be Adopted To Manage Customer Defections Andmentioning
confidence: 99%
“…Colgate et al, 1996;Colgate and Hedge, 2001;Keaveney, 1995) and the significance of switching behaviour (Fornell and Wernerfelt, 1987;Reichheld and Sasser, 1990;Mittal and Lassar, 1998). Other studies have investigated why customers do not always defect to competing providers.…”
Section: Customer Retention In Consumer Marketsmentioning
confidence: 99%